Wo(men) at work? The impact of cohabiting and married partners' earning on women's work hours - Doreen Triebe (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This study investigates the determinants of women's labor supply in the household context. The main focus is on the effect of a change in male partner's wages on women's work hours. This is linked to the broader question of whether married and cohabiting women make different economic decisions and respond differently to changes in their partners' wages. In addition, this study seeks to connect the working behavior of married and cohabiting individuals to the tax-splitting benefit for married couples. To provide a complete picture of working behavior within households, I analyze both women and men using data from the German Socio-Economic Panel Study (SOEP) from 1993 to 2010. The methodology for the main analysis relies on fixed effects regression. The main estimation results suggest that married women work less on the labor market and further, an increase in partner's wages results in a negative and significant effect on married women's work hours. The marital status of men, on the other hand, has no significant impact on their work hours.
Keywords: D13; J12; J22; 330; women's work hours; division of labor; cohabitation vs. marriage